2010
DOI: 10.1590/s1413-41522010000300005
|View full text |Cite
|
Sign up to set email alerts
|

Alternativas para o controle de emissões odorantes em reatores anaeróbios tratando esgoto doméstico

Abstract: Esta nota técnica busca consolidar as principais características, vantagens e desvantagens dos métodos usualmente empregados para o controle de emissões odorantes, discorrendo criticamente acerca da aplicabilidade de cada um dos métodos para o tratamento de odores em estações de tratamento de esgoto doméstico. Verificou-se que vários métodos são sofisticados, de elevado custo e, muitas vezes, não aplicáveis ao tratamento de odores emitidos em reatores anaeróbios tratando esgoto doméstico. Uma análise qualitati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
1
29

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(43 citation statements)
references
References 8 publications
0
13
1
29
Order By: Relevance
“…The higher efficiencies obtained with the DC technique in the present research (around 80%) are comparable to the ones reported by Kobayashi (1983), which ranged between 81 and 95%, using however the biochemical technique (photosynthetic bacteria) for dissolved sulfide removal. The efficiencies of the present study are also much higher than the ones obtained by Krayzelova et al (2014), with the micro aeration technique, of around 16%, and by Souza (2010), with the dissipation chamber technique, of around 40%, using however different operational conditions: free drop height = 0.45 m; number of renovations = 11 h -1 ; and hydraulic loading rates varying between 0.048-0.060 m 3 .m -2 .min -1 . In addition, analyses of H 2 S in the waste gas indicated concentrations varying from 100 to 500 ppm (Figure 8), confirming the release of part of the dissolved sulfide to the headspace of the DC.…”
Section: Dissipation Chamber (Dc)contrasting
confidence: 58%
“…The higher efficiencies obtained with the DC technique in the present research (around 80%) are comparable to the ones reported by Kobayashi (1983), which ranged between 81 and 95%, using however the biochemical technique (photosynthetic bacteria) for dissolved sulfide removal. The efficiencies of the present study are also much higher than the ones obtained by Krayzelova et al (2014), with the micro aeration technique, of around 16%, and by Souza (2010), with the dissipation chamber technique, of around 40%, using however different operational conditions: free drop height = 0.45 m; number of renovations = 11 h -1 ; and hydraulic loading rates varying between 0.048-0.060 m 3 .m -2 .min -1 . In addition, analyses of H 2 S in the waste gas indicated concentrations varying from 100 to 500 ppm (Figure 8), confirming the release of part of the dissolved sulfide to the headspace of the DC.…”
Section: Dissipation Chamber (Dc)contrasting
confidence: 58%
“…São sistemas de tratamento baseados na rota natural de mineralização, e com o tempo, vão se tornar soluções de desenvolvimento sustentável, sendo que entre seus coprodutos, principalmente o metano possui grande potencial energético (CHERNICHARO et al, 2010).…”
Section: Emissões De Sulfeto De Hidrogênio Em Reatores Anaeróbiosunclassified
“…Nos casos onde não existem medidas para minimização dos efeitos dos gases odorantes, ou onde essas medidas não são eficientes, há a necessidade de se programar uma tecnologia de tratamento desses gases (SILVA, 2008;SCHIRMER, 2008). Chernicharo et al (2010) constataram que os métodos para o controle de gases odorantes em estações de tratamento de esgoto podem ser caracterizados como de natureza física, química e bioquímica. Para eles os processos químicos e físicos já vêm sendo desenvolvidos a mais tempo do que os processos biológicos.…”
Section: Processos De Tratamento De Sulfeto De Hidrogêniounclassified
See 1 more Smart Citation
“…De acordo com a experiência brasileira (CHERNICHARO & STUETZ, 2008), as possíveis melhorias relacionadas a projeto, construção e operação de reatores UASB aplicados ao tratamento de esgoto doméstico podem ser agrupadas de acordo com os tópicos mostrados na Figura 1. Embora melhorias para todos os tópicos mostrados na referida figura estejam correntemente sendo investigadas, no presente trabalho são enfocadas apenas as melhorias relacionadas ao tratamento das emissões odorantes.…”
Section: Introductionunclassified